Usage Patterns, Trust Generated, and Influence of Information in Internet and Social Media on Decision-Making by Patients Diagnosed With Rheumatic Diseases in Latin America. - Chaparro, Camilo Andrés; Fernández-Ávila, Daniel G; Fuentes, Yurilis; Ferreyra, Leandro; Brance, María L; Muñoz, Oscar Mauricio (Clinical Medicine Insights: Arthritis & Musculoskeletal Disorders, 2025)
Introduction: Internet and social media are widely available tools for several purposes, including search of health information. This study aims to describe the usage patterns, the trust generated, and the influence of such information on decision-making by patients diagnosed with systemic lupus erythematosus and rheumatoid arthritis. Methods: A cross-sectional study was conducted, administering a survey to patients with rheumatic diseases at multiple centers in Latin America, virtually or on paper. Three domains were evaluated: access/patterns of use, perception, and confidence generated by the health information found. Subgroup analysis based on key characteristics was performed. Results: In total, 244 surveys were analyzed, identifying 96.7 % respondents as regular internet users, mainly through smartphones (79.5%). About 86.5% used social media regularly, around 15.2 % used it for finding health information. YouTube was the most frequently used (67.6%). 64.3 % perceive searching information as straightforward and 65.6% as not frustrating; academic institutions were the most and "influencers" were the least trusted. Most expressed high confidence in the ability to use information and perceive it as beneficial. Different patterns of use, perception, and confidence were identified according to disease, age, educational level, country of origin and survey method of collection. Conclusions: This study illustrates the high prevalence of Internet and social media access in Latin America, primarily through mobile devices, which represents an opportunity to develop educational strategies for the population that have access to these tools. These strategies can be tailored according to specific use patterns and differential characteristics of distinct subgroups of patients. Plain language summary: The internet and social media are popular tools that people use for many reasons, including looking for health information. This study looked at how patients with systemic lupus erythematosus and rheumatoid arthritis use the internet and social media, how much they trust the health information they find, and how it influences their decisions about their health. Patients with these conditions were surveyed across Latin America, both online and on paper. They asked questions about how often and why they use the internet and social media, how confident they feel in the information they find, and how much they trust different sources of information. Out of 244 people surveyed, almost all (96.7%) used the internet regularly, mostly on smartphones. Most also used social media, though only 15% used it specifically for health information. YouTube was the most popular platform. Most participants found it easy to search for health information, and most did not find it frustrating. They trusted information from universities the most and from social media influencers the least. People generally felt confident using the health information they found and thought it was helpful. The study showed that there are different ways people use and trust the internet based on their disease, age, education, country, and how they completed the survey. This provides a chance to create better educational tools for these patients, tailored to their specific needs and habits.